SCHOOL BUILDING UTILIZATION ANALYSIS NET ZERO CARBON IN JAKARTA ELEMENTARY AND HIGH SCHOOL - Rizka Zamzani Ibrahim; Eleonora Sofilda (Journal of Social Research, 2024)
This research aims to analyze the utilization of Net Zero Carbon school buildings in primary and secondary schools in Jakarta and its implications on students' green behavior and the involvement of various stakeholders in supporting the net zero school program in efforts to reduce emissions in the city of Jakarta. This study employs qualitative methods, gathering data through questionnaires, interviews, and document studies. The findings indicate that, besides producing a low Energy Consumption Index or being energy efficient, Net Zero Carbon schools also have a positive impact on increasing students' awareness and sustainable behaviors. Stakeholder engagement is found to be crucial in supporting the implementation and success of this initiative. These findings provide insights for further development in sustainable building in the education sector